2020
DOI: 10.1186/s12886-020-01471-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of virtual reality on visual parameters: immersive versus non-immersive mode

Abstract: Background: To investigate the differences in refraction, accommodative factors, visual parameters, and subjective symptoms after using two types of virtual reality (VR) content with different depths of perception. Methods: Twenty-three volunteers, who played VR games in two modes (immersive and non-immersive) for 30 min, were enrolled. Visual parameters were examined before and after using VR. Accommodative factors were measured using static and dynamic methods. Subjective symptoms were assessed using a quest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
(37 reference statements)
0
30
1
6
Order By: Relevance
“…Furthermore, a higher accommodative lag may not have worsened because of the ceiling effect. In our previous study, we found that 30 min of VR SHMD use increased the accommodative lag in subjects with exophoria 5 . However, there was no correlation between exophoric deviation and accommodative lag in this study.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Furthermore, a higher accommodative lag may not have worsened because of the ceiling effect. In our previous study, we found that 30 min of VR SHMD use increased the accommodative lag in subjects with exophoria 5 . However, there was no correlation between exophoric deviation and accommodative lag in this study.…”
Section: Discussionmentioning
confidence: 81%
“…The following 13 symptoms were included in the questionnaire that was based on a computer vision syndrome questionnaire, which was previously reported by Seguí Mdel et al 5 , 12 : dry eye symptoms (burning, feeling of a foreign body, excessive blinking, tearing, dryness, tingling, and increased sensitivity to light), visual disturbance (blurred vision, double vision, and difficulty focusing for near vision), and neurological symptoms (headache, dizziness, and nausea). The symptom sensation questionnaire included six identical analog scales (0 = none to 6 = too severe to tolerate), and the subject recorded the magnitude of each symptoms compared relative to that at the baseline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors exerting short-term effects include food or fluid intake, changes in systemic blood pressure, and vigorous physical activity. Although most factors affecting IOP are random and inherently unstable 11 , the resulting short-term effects are observable for a limited period.In previous studies, the effects of immersive VR devices on visual parameters are all focused on the visual effects after 30 min of use [3][4][5][6][7] . However, it takes about 10 min to get into immersion using VR mobile devices.…”
mentioning
confidence: 99%